The contribution of human resources to e-commerce capability and business performance: a structural equation modelling. (1st January 2012) - Jehangir, Muhammad; Dominic, P.D.D.; Khan, Alamgir; ,
E-commerce (EC) not only holds the opportunities for business growth but also posses the challenges. These challenges have a significant impact on EC success. By examining drivers of business performance in EC from a firm's resource perspective, the author conceptualises three antecedents of firm's human resources that are critical for business performance in EC-based business: managerial expertise, top management support and learning capability. Defining EC capability by firm's human resources it is expected that EC have a significant contribution to business performance (financial and non-financial performance). In this paper, we have proposed a conceptual framework to find out the human resource attributes and its contribution in developing firm's EC capability which lead to better performance. In effect this research provides a checklist for managers to utilise the human resources and redesign their strategies for the successful EC technology implementation and usage.